Orientasi Kewirausahaan dan Pasar sebagai Determinan Faktor Pascapanen Lada Muntok oleh Petani - Evahelda Evahelda; Iwan Setiawan; Rati Purwasih; Rufti Puji Astuti (Society, 2021)
The problem of Muntok Pepper business performance continues to decline due to the inability of farmers to face price uncertainty, recognize and understand market conditions. The fact is that the number of business actors continues to grow. Competing to face changes in the business environment is necessary, so entrepreneurial farmers are needed. This study aims to look at the postharvest process carried out by Muntok Pepper farmers and analyze whether entrepreneurial orientation and market orientation are determinant factors that affect the postharvest handling process. The research method used a survey method involving 60 farmers. Using Structural Equation Modeling (SEM), data analysis was carried out using smart Partial Least Squares (PLS). The results showed that the postharvest handling process was significantly influenced by entrepreneurial orientation and market orientation, but entrepreneurial orientation influence was greater than market orientation. Farmers carry out postharvest handling of Muntok Pepper in two stages. 50% of farmers carry out threshing, soaking, and drying processes. 50% of farmers do not do the sorting, grading, and milling process. Farmers’ decisions in postharvest handling are more influenced by the influence of the entrepreneurial orientation of farmers. Farmers who are motivated to excel, dare to take risks, and are willing to innovate by using new production methods tend to carry out a good postharvest handling process, not only threshing, soaking, and drying but also sort and process pepper derivative products.